Arthropod fauna associated an rice field in Caucasia – Colombia (Revista Sistemas de Producción Agroecológicos, 2024)
Rice is a crop of great economic and social importance in Colombia, being the main source of income for 20% of the country's municipalities. Generally, producers resort to using chemical synthesis products to control arthropod pests, without considering other strategies or key concepts in integrated management such as the threshold action  or economic. In addition, many are unaware of the presence of natural enemies of organisms harmful to the crop. Arthropod collection was carried out using: a pitfall trap and entomological net in a rice field in the municipality of Caucasia, Antioquia. 47 species of arthropods belonging to nine orders and 28 different families were recorded. The most representative orders were Hymenoptera, Hemiptera, Coleoptera and Araneae. 25 of these species were considered potential predators of arthropods, nine were classified as pests, especially of the order Hemiptera, and the remaining were considered neutral to the crop or beneficial to it. This work made it possible to inform some producers in the municipality about the diversity of their crops, encouraging them to protect this valuable resource. We believe that it is necessary to promote more studies in the area that will allow us to know the true diversity of the arthropofauna associated with the crop in Caucasia, Antioquia, and thus promote awareness campaigns on the protection of beneficial organisms to the rice guild.
Keywords: biodiversity; natural enemies; Oryza sativa; spiders